Moderate Range Static Magnetic Field Promoted Variation of Blood Parameters: An In vitro Study - Mustafa, Bestoon T.; Yaba, Sardar P.; Ismail, Asaad H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
This study was undertaken to investigate the influence of a homogenous and uniform static magnetic field (SMF) on the main blood cell counts in vitro experiment. Fresh blood samples were collected from albino rats and exposed to SMF (2.4, 6, 25, 50, 75, and 100 mT) versus 15–60 min. Results showed a significant change of blood counts under the low field effects. A 2.4 mT was a trend of white blood cells (WBCs) count increase non-linearly. However, a 6 mT exposure reduced WBCs with about 39%. Other variations fluctuated within 30%. The 25 mT decreased red blood cells (RBCs), hemoglobin, and hematocrit levels with 13% similarly. The lower exposure field, (2.4 and 6) mT, and effects on RBCs were 6% fluctuation. The 6 mT reduced platelet counts with half in comparison to control blood samples. About 20% increase obtained due to 50 mT exposure during all period. None of 75 and 100 mT exposures dominated blood counts alterations. The quiet magnetic field exposure for a certain time can be interesting to control blood cell count-related diseases.